2021
DOI: 10.1007/s10853-021-06168-7
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of adsorption sensitivity of Au-doped MoS2 gas sensor to main characteristic gases in oil

Abstract: Detecting oil-dissolved gases in transformer is crucial for internal discharge fault diagnosis. Methane (CH 4 ), acetylene (C 2 H 2 ), ethylene (C 2 H 4 ), ethane (C 2 H 6 ) are some of the important fault characteristic gases in oil-immersed transformer discharge faults. The concentration and production rate can effectively reflect the insulation performance of oil-paper power transformer. In order to realize the effective detection of gases in the oil, the Au atom-doped MoS 2 (Au-MoS 2 ) monolayer was propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 35 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…The strong interaction is required to retain the gas molecule on the substrate surface, and weak interaction is necessary for removing of gas molecules from the substrate without damaging the substrate’s properties. 19 , 54 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong interaction is required to retain the gas molecule on the substrate surface, and weak interaction is necessary for removing of gas molecules from the substrate without damaging the substrate’s properties. 19 , 54 …”
Section: Resultsmentioning
confidence: 99%
“… 26 28 To boost the sensitivity of semiconductor-based gas sensors, low dimensionality and easily adjustable features of two-dimensional (2D) materials 29 31 have enchanted intensive research in inorganic 32 35 and organic 36 38 gas identification. 2D materials for example graphene, 39 43 phosphorene, 26 , 44 , 45 stanene, 46 48 arsenene, 49 silicone, 50 , 51 borophene, 52 , 53 molybdenum disulfide (MoS 2 ), 13 , 54 60 tungsten disulfide (WS 2 ) 61 monolayers have been investigated for the adsorption of small gas molecules and VOCs as well. Numerous compounds, elemental crystals, and atomically thin materials with exceptional electronic and mechanical properties are formed by lighter elements such as carbon (C), boron (B), and nitrogen (N).…”
Section: Introductionmentioning
confidence: 99%
“…The electrical conductivity (σ) ,,, of the SnS 2 systems can be calculated by σ exp ( E normalg / 2 k normalB T ) where E g , k B , and T represent the band gap of SnS 2 systems, the Boltzmann constant, and the thermodynamic temperature correspondingly.…”
Section: Methodsmentioning
confidence: 99%
“…Since then, the gas sensing properties of graphene-like 2D materials, , stanene, silicene, , transition metal oxides (TMOs), and transition metal dichalcogenides (TMDs) , have been substantially studied. Thanks to their superior semiconducting behavior, strong reactivity, high carrier mobility, and high surface-to-volume ratio, TMD monolayers, especially MoS 2 , MoSe 2 , and PtTe 2 , ,,,, have become a focus of attention for gas sensing applications. , Similar to TMDs, SnS 2 monolayer possesses desirable semiconducting characteristics with an indirect band gap of 1.57 eV, high on/off ratio of 10, 8 and exceptional carrier mobility of 50 m 2 V –1 s –1 ,, that are similar to TMD monolayers, indicating its effective application in gas sensing . Ou’s study revealed that the SnS 2 monolayer exhibits favorable sensing abilities for NO 2 gas, while another research by Guo also demonstrates SnS 2 monolayer’s selectivity and desirable sensitivity toward SF 6 decomposition gases .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to traditional gas sensors, the use of nanomaterial sensors for the detection of gas type and gas content has the advantages of small size, fast response, high sensitivity and low costs. Tao et al explored the use of nanomaterial sensors, both in theory and experimentally [ 17 , 18 , 19 , 20 , 21 ]. Thanks to their large surface areas and adequate adsorption sites, 2D materials are increasingly being used as gas adsorbents and sensors and were studied by Gui et al [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%